PENGARUH UKURAN PERUSAHAAN, EARNING PER SHARE, DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS DENGAN PERTUMBUHAN LABA SEBAGAI PEMODERASI PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI PT. BURSA EFEK INDONESIA TAHUN 2011-2012 - Saut Parulian; Restu Agusti; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted to examine the effect of company size , firm size are moderated earnings growth , debt to equity , debt to equity are moderated growth in earnings , earnings per share and earnings per share earnings growth moderated affect the profitability of the company. The population in this study areall food & beverage companies listed in Indonesia Stock Exchange ( IDX ) . Sampling was done by using purposive sampling method, namely the determination of the sample with the target or specific considerations. The Company elected to the sample in this study is based on these criteria are as manyas 33 companies. Analysis of data using multiple regesi method. The results of company size (X1) does not have a significant effect on the profitability of the company . Debt to Equity Ratio /DER (X2) has a significant effect on the profitability of the company. Earning Per Share /EPS (X3) has a significant effecton the profitability of the company. Size companies which is moderated by profit growth in earnings (X4) has no significant effect on the profitability of the company. Debt to Equity Ratio moderated by profit growth (X5) has no significant effect on the profitability of the company. Earning Per Share moderated by profit growth (X6) does not have a significant effect on the profitability of the company. The profitability explained by the variable i.e. company size, DER , EPS , debt to equity ratio and profit growth as moderating variables is equal to 67.3 %. Whileapproximately 22.7 % influenced by other variables not examined in this study, such as working capital, liquidity and firm age.Keywords : Company Size, Debt to Equity Ratio, Earnings Per Share, Company Size Moderated by Profit Growth, Debt to Equity Ratio Moderated by Profit Growth, Earnings Per Share Moderated by Profit Growth, Profitability